Spectral characterization and intracellular detection of Surface‐Enhanced Raman Scattering (SERS)‐encoded plasmonic gold nanostars. (5th October 2012) - Yuan, Hsiangkuo; Fales, Andrew M.; Khoury, Christopher G.; Liu, Jesse; Vo‐Dinh, Tuan
<x xml:space="preserve">Abstract</x> Plasmonic gold nanostars offer a new platform for surface‐enhanced Raman scattering (SERS). However, due to the presence of organic surfactant on the nanoparticles, SERS characterization and application of nanostar ensembles in solution have been challenging. Here, we applied our newly developed surfactant‐free nanostars for SERS characterization and application. The SERS enhancement factors (EF) of silver spheres, gold spheres and nanostars of similar sizes and concentration were compared. Under 785 nm excitation, nanostars and silver spheres have similar EF, and both are much stronger than gold spheres. Having plasmon matching the incident energy and multiple 'hot spots' on the branches bring forth strong SERS response without the need to aggregate. Intracellular detection of silica‐coated SERS‐encoded nanostars was also demonstrated in breast cancer cells. The non‐aggregated field enhancement makes the gold nanostar ensemble a promising agent for SERS bioapplications. Copyright © 2012 John Wiley & Sons, Ltd.